Il teatro greco sulla scena italiana. La linea Ronconi-Castri - Roberto Alonge (Il castello di Elsinore, 2016)
The paper aims to analyze the relationship between Greek theatre and Italian mise-en-scène. Roberto Alonge examines two examples of two more important directors, Luca Ronconi and Massimo Castri (as everybody knows, Giorgio Strehler never was interested in Greek authors), Medea and Alcesti written by Euripide. Obviously both directors avoid a philological approach and exploit the Greek dramaturgy to express oneself, their fantasies. A male actor, Franco Branciaroli, acts in the role of Medea: that shows the fine misogyny of Luca Ronconi. Alcesti, on the contrary, emphasizes the strange Castri’s feminism, if this term is permitted.